Apheresis for chimeric antigen receptor T‐cell production in adult lymphoma patients. Issue 8 (19th July 2022) - Harrer, Dennis Christoph; Heidenreich, Martin; Fante, Matthias Alexander; Müller, Viktoria; Haehnel, Viola; Offner, Robert; Burkhardt, Ralph; Herr, Wolfgang; Edinger, Matthias; Wolff, Daniel; Thomas, Simone; Brosig, Andreas
Abstract: Background: To date, in‐depth analysis of leukapheresis products as starting material for CAR T‐cell manufacturing, specifically Tisagenlecleucel production, are scarce. In this study, we report on lymphapheresis data for production of Tisagenlecleucel for elderly and pretreated lymphoma patients. Study Design and Methods: Spectra Optia from Terumo BCT, Lakewood, CO, was employed for apheresis using the cMNC program. Apheresis success was defined as meeting a target total nucleated cell (TNC) count of ≥2 × 10 9, a CD3‐positive lymphocyte count of ≥1 × 10 9 and an overall viability of ≥70% in the lymphapheresis product. Results: Twenty‐three patients (age 37–77 years) and 24 apheresis runs were evaluated. The median CD3‐positive lymphocyte count in peripheral blood at the beginning of apheresis was 565 cells/μl (range: 70–1345 cells/μl). Circulating lymphoma cells were detected in one patient prior to apheresis. Target criteria were met in 21 of 23 patients. The median TNC count in the apheresate was 11.2 × 10 9 (range: 2.9 × 10 9 –47.4 × 10 9 ). The median CD3‐positive lymphocyte count in the apheresate was 2.55 × 10 9 (range: 0.370 × 10 9 –6.915 × 10 9 ), which resulted in a median collection efficiency for CD3‐positive lymphocytes of 63.7% (range: 9.56%–93.6%). No adverse events associated with the apheresis process were observed. Conclusions: Lymphapheresis with the Spectra Optia cMNC program provided a sufficient quantity of CD3‐positive lymphocytes for CAR T‐cell manufacturing for the majority of patients despite their heavy pretreatment and advanced age. Moreover, we are the first to advocate early pre‐emptive lymphocyte collection in DLBCL‐NOS patients intended to undergo treatment with Tisagenlecleucel.